Analisis Strategi Pengendalian Paparan Bahan Toksik melalui Program Higiene Industri dan Keselamatan Kerja - Aprilyautami Aprilyautami; Muhammad Ramadhan Ginting; Rabbaniyah Rabbaniyah; Abdurrozzaq Hasibuan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Exposure to toxic materials in the workplace remains a major occupational health and safety issue, particularly in industrial sectors with high chemical use intensity. Various control efforts have been implemented through industrial hygiene and occupational safety (OHS) programs, but their effectiveness varies. This study aims to analyze strategies for controlling toxic material exposure through industrial hygiene and OHS programs based on literature review over the past five years. The method used was literature review of 10 national journals relevant  the topic of toxic material exposure in various industrial sectors. The analysis results indicate that toxic material exposure is still found in various sectors, with types of materials such as heavy metals, organic solvents, toxic gases, and industrial dust. The most commonly implemented control strategies are the use personal protective equipment (PPE), administrative controls, and some engineering controls such as ventilation. However, the effectiveness of these controls is less than optimal due low worker compliance, limited supervision, and the minimal implementation of higher-level controls such as elimination and substitution. Therefore, it is necessary to strengthen integrated industrial hygiene programs, improve worker compliance, and implement a more comprehensive hierarchy of controls to minimize the risk of toxic material exposure in the workplace.